Bundists and the issue of emigration from Poland after the Second World War - Rusiniak-Karwat, Martyna (European Spatial Research and Policy, 2021)
The main objective of this paper is to present a change in the attitudes among Bundists towards emigration in the post-war Poland. The program of the Jewish Labour Bund throughout its existence was based on three pillars: here-ness (doykayt), family-ness (mishpokhedikayt), and Jewish-ness (Yiddishkayt). After the Second World War some of them lost their significance. Many Jews, including Bundists, saw their future outside Poland. In the article I will show different attitudes of the members of the Bund towards emigration, as well as the reasons behind their choices: either to stay in Poland or to leave the country.